Freezing characteristics of air-entrained concrete in the presence of deicing salt. (August 2015) - Liu, Zhichao; Hansen, Will
Abstract: The interaction between a salt solution and ice formation in capillary pores might provide new insight into the salt frost scaling process. To accomplish this small prismatic specimens (10 mm × 10 mm × 90 mm) were cut from air-entrained concrete, dried at 50 °C until constant weight, then immersed in sodium chloride (NaCl) solutions of different concentrations (0%, 3%, 9% and 12%) until they reached full capillary saturation. They were then subjected to a freeze–thaw (F–T) cycle in a high resolution low temperature dilatometer (LTD) with the surface temperature and uniaxial length-change continuously monitored. Internal saturation of capillary pores with increasing salt solutions is found to have a profound effect on the F–T response including the temperature rise and instant dilation associated with ice nucleation. It is concluded that salt ions retard ice formation and the effect of ice-growth on pore expansion during an F–T cycle. The presence of salt ions in the concrete pores and surface liquid has a counter-balancing effect on specimen length-change associated with ice-growth, which may provide one possible explanation for the pessimum salt concentration effect. The extent of surface scaling is also affected by the intrinsic capillary transport property (i.e., sorptivity) of the porous cementitious binder. Salt scaling is exacerbated in concretes with increasing sorptivity.